Weedon's skin pathology essentials - Johnston, Ronald (Elsevier, 2024)
Comprehensive, concise, and superbly illustrated, Weedon’s Skin Pathology Essentials, 3rd Edition, provides expert, easy-to-read guidance on key diagnoses in dermatopathology for pathologists and dermatologists in practice and training. This clearly written, well-structured text/atlas is ideal for quickly looking up practical problems in the recognition and diagnosis of skin lesions both clinically and histologically. Covers more than 1,300 dermatopathological entities, both common and rare, including additional entries in every section of the text. Provides more than 3,000 color histopathologic and clinical images for complete visual coverage of key diagnostic points for any given entity, and features new illustrations of rare conditions and unusual manifestations. Includes numerous summary tables and diagnostic algorithms that guide you to the most likely diagnosis and set of differential diagnoses for numerous inflammatory and neoplastic skin conditions. E-Book allows you to access all of the text, figures, and references.